Ta có: \(\overrightarrow {OA} = \overrightarrow {OG} + \overrightarrow {GA} \); \(\overrightarrow {OB} = \overrightarrow {OG} + \overrightarrow {GB} \); \(\overrightarrow {OC} = \overrightarrow {OG} + \overrightarrow {GC} \)
\(\begin{array}{l} \Rightarrow \overrightarrow {OB} + \overrightarrow {OA} + \overrightarrow {OC} = \overrightarrow {OG} + \overrightarrow {GA} + \overrightarrow {OG} + \overrightarrow {GB} + \overrightarrow {OG} + \overrightarrow {GC} \\ \Leftrightarrow \overrightarrow {OB} + \overrightarrow {OA} + \overrightarrow {OC} = 3\overrightarrow {OG} + \left( {\overrightarrow {GA} + \overrightarrow {GB} + \overrightarrow {GC} } \right)\end{array}\)
Do G là trọng tâm của tam giác ABC nên \(\overrightarrow {GB} + \overrightarrow {GA} + \overrightarrow {GC} = \overrightarrow 0 \)
\(\begin{array}{l} \Rightarrow \overrightarrow {OB} + \overrightarrow {OA} + \overrightarrow {OC} = 3\overrightarrow {OG} + \overrightarrow 0 \\ \Leftrightarrow \overrightarrow {OB} + \overrightarrow {OA} + \overrightarrow {OC} = 3\overrightarrow {OG} \end{array}\)